Las compras verdes, una práctica sustentable y ecológica: posibilidad de su aplicación en el Perú - García Paz, Jorge (2009)
Green purchases are part of a strategy for the application of a sustainable country development, considered as ‘a development that satisfies the people’s current necessities without affecting the ability of future generations to satisfy their own’. (Brundtland Report 1987). In the same way, it is part of a strategy to fight the effects of the weather changes or greenhouse that affect our planet and as a consequence the humanity.The green or ecological purchases are simple practices in the developing countries, in most cases in the European countries, but they are not known in Latin American countries. Just Costa Rica is supporting this practice with public institutions, for that reason they will get considerable benefits in its process.The Peruvian government is conformed by more than two thousand public entities, they are formed as national and regional government entities, town halls, decentralized offices, entities in the scope of FONAFE, business treatment and charitable work. These entities programmed purchases in the year 2008 approximately 58.234 million soles. However, just a few of the purchases had an ecological purpose.The following article has the objective to show the benefits of the green or ecological purchases, and the experience in developed countries to decide its application in Peru. In this way, this study pretends to join a number of experiences of countries in their green purchases and so it is divided in four parts. The first part referrs to the framework of the green purchases and it refers to the different concepts that explain those factors that push the United States to apply this strategy. The second part is about the international experience with the best practices. The third part shows the possibility of the green purchases in the country, and in the fourth part conclusions are presented.